Evaluating the Effectiveness of Fiber Reinforced Polymer (FRP) in Structural Strengthening: A Meta-analysis - Agus Triyono; Tri Satriawansyah; Aris Krisdiyanto (AKADEMI TEKNIK ADI KARYA, 2024)
This study aims to evaluate the effectiveness of Fiber Reinforced Polymer in strengthening structures. This research is a type of meta-analysis research. The data source comes from 9 studies sourced from google scholar, DOAJ, ProQuest and Fronteins published in 2023-2024. Data selection techniques through the PRISMA method in 2020. The data analysis in this study is to calculate the effect size value with the help of the STATA application. The results of this study concluded that the application of Fiber Reinforced Polymer had a positive effect on the strengthening of the structure with an effect size value = 0.813 with a high effect size category. This finding explains that the application of fiber reinforced polymer is effective in strengthening concrete structures in civil engineering.